AMOTL2 restrains transforming growth factor‐β1‐induced proliferation and extracellular matrix deposition of airway smooth muscle cells via the down‐regulation of YAP1 activation. Issue 11 (29th July 2021) - Fang, Ping; Deng, Wen‐jing; Fan, Na; Shi, Jie; Shi, Hong‐yang; Ou, Ling; Pan, Jian‐li; Yang, Shuan‐ying
Abstract: Angiomotin‐like 2 (AMOTL2) is a key modulator of signaling transduction and participates in the regulation of various cellular progresses under diverse physiological and pathological conditions. However, whether AMOTL2 participates in asthma pathogenesis has not been fully studied. In the present work, we studied the possible role and mechanism of AMOTL2 in regulating transforming growth factor‐β1 (TGF‐β1)‐induced proliferation and extracellular matrix (ECM) deposition of airway smooth muscle (ASM) cells. Our results showed marked reductions in the abundance of AMOTL2 in TGF‐β1‐stimulated ASM cells. Cellular functional investigations confirmed that the up‐regulation of AMOTL2 dramatically decreased the proliferation and ECM deposition induced by TGF‐β1 in ASM cells. In contrast, the depletion of AMOTL2 exacerbated TGF‐β1‐induced ASM cell proliferation and ECM deposition. Further research revealed that the overexpression of AMOTL2 restrained the activation of Yes‐associated protein 1 (YAP1) in TGF‐β1‐stimulated ASM cells. Moreover, the reactivation of YAP1 markedly reversed AMOTL2‐mediated suppression of TGF‐β1‐induced ASM cell proliferation and ECM deposition. Together, these findings suggest that AMOTL2 restrains TGF‐β1‐induced proliferation and ECM deposition of ASM cells by down‐regulating YAP1 activation.